Effect of successive flowering on white clover seed yield - Domingues, Heber Comes; Nabinger, Carlos; Paim, Nilton Rodrigues (Pesquisa Agropecuaria Brasileira, 1991)
Seed production and seed yield components of Jacuí white clover (Trifolium repens L.) cultivar was recorded for different harvest dates which were chosen according to the flowering behaviour of this species. The experiment was carried out at EEA-UFRGS, Guaíba, RS, Southern Brazil. Assessment was made by harvesting at the following times: the first flowering period (F1); accumulated values for F1 and the second flowering period (F2); and accumulated values for F1 + F2 + the third flowering period (F3). Three more harvests were made for the F1 period, two more for the F2 period and one more for the F3 period. In total, nine, harvests were made. The results indicate that accumulated flowering is not an efficient cultural practice to increase the seed yield. More than one harvest made on the same sward only showed advantages when done after the F1 period. Defoliation (cutting or close date) in the middle of November (in Southern Brazil) appears to be an important cultural practice for the increase of seed yield. The number of ripe inflorescences per unit area at harvest seemed to be the main character contributing to increase seed yield.